ANALISIS STRATEGI DAN MEDIA PEMBELAJARAN BERBASIS AUDIO VISUAL PADA MATA PELAJARAN FIQIH KELAS X DI MAN 2 MODEL MEDAN - Haidir Haidir; Dzul Fadli Sya’bana; Ika Wirdani; Mariyati Mariyati; Nur Khafifah Indriyani Batubara; Saripah Aini; Hadi Sufyan (Raudhah - Proud To Be Professional, 2023)
Abstract This research is based on the teaching methods used by instructors to ensure that examples can run successfully, effectively, and ideally. Furthermore, it is followed by an evaluation carried out by educators as an effort to achieve the standard of elementary student achievement. The subjects of this study are Fiqh teachers of Class X, the witness chairman, the Deputy Head for the Framework, and substitute students. The information collection procedures consist of interviews, observations, and documentation, using the information approval method through triangulation procedures. The information examination methods include information reduction (determination of information), information display (presentation of information), and drawing conclusions/confirmation (drawing conclusions).The research findings from this study indicate that (1) the educational methodology applied by the instructors in Class X of Man 2 Model Medan, which involves a well-structured classroom system, is evident from the growing organized experience, students' clear understanding, combined with the well-organized and neat condition of the homeroom teacher, serves as one variable that motivates students in enhancing their growing experiences. Students contribute to maintaining the beauty of the classroom by filling it with their works and making student activities a priority during the teaching and learning process. To regulate the airflow and avoid obstructing the educational experience, the windows are kept open and air ventilation is consistently cleaned